APP-CD74 axis mediates endothelial cell-macrophage communication to promote kidney injury and fibrosis - Liu, Bin; Li, Faping; Wang, Yuxiong; Gao, Xin; Li, Yunkuo; Wang, Yishu; Zhou, Honglan (Frontiers in Pharmacology, 2024)
Background: Kidney injuries often carry a grim prognosis, marked by fibrosis development, renal function loss, and macrophage involvement. Despite extensive research on macrophage polarization and its effects on other cells, like fibroblasts, limited attention has been paid to the influence of nonimmune cells on macrophages. This study aims to address this gap by shedding light on the intricate dynamics and diversity of macrophages during renal injury and repair.During the initial research phase, the complexity of intercellular communication in the context of kidney injury was revealed using a publicly available single-cell RNA sequencing library of the unilateral ureteral obstruction (UUO) model. Subsequently, we confirmed our findings using an independent dataset from a renal ischemia-reperfusion injury (IRI) model. We treated two different types of endothelial cells with TGF-β and co-cultured their supernatants with macrophages, establishing an endothelial cell and macrophage co-culture system. We also established a UUO and an IRI mouse model. Western blot analysis, flow cytometry, immunohistochemistry and immunofluorescence staining were used to validate our results at multiple levels.Results: Our analysis revealed significant changes in the heterogeneity of macrophage subsets during both injury processes. Amyloid β precursor protein (APP)-CD74 axis mediated endothelialmacrophage intercellular communication plays a dominant role. In the in vitro co-culture system, TGF-β triggers endothelial APP expression, which subsequently enhances CD74 expression in macrophages. Flow cytometry corroborated these findings. Additionally, APP and CD74 expression were significantly increased in the UUO and IRI mouse models. Immunofluorescence techniques demonstrated the co-localization of F4/80 and CD74 in vivo.Our study unravels a compelling molecular mechanism, elucidating how endotheliummediated regulation shapes macrophage function during renal repair. The identified APP-CD74 signaling axis emerges as a promising target for optimizing renal recovery post-injury and preventing the progression of chronic kidney disease.